As formas identitárias nos contextos de trabalho: uma análise da profissionalidade docente - Oliveira, Lúcia Matias da Silva (2014)
This work aims the construction of sociological portraits that restore processes of socialization, as a method for the analysis of the interactions the teacher performs and how they potentiate his/her dispositions from the generating principle of habitus in order to respond to the daily challenges in the classroom and the school, changing the teacher identity in the contexts of workin this process. The hypotheses were based in presupposition that admit the reconfiguration of the teacher identity from the interactions in the contexts of work which lead him/her to accept actions and attitudes that come from dispositions dependent of thehabitus. This work aims to investigate these elements by means of the construction of sociological portraits of three teachers from Primary School, registering their individual trajectories; semi-structured interviews were used, planned according to a conceptual grid that allowed the elaboration of guidelines constituted by six categories: family, school, work, sociability, leisure/culture and body: each teacher answered 160 questions in 37 hours of interview. The data collection was accomplished in the second semester of 2012, after a model interview to test the instrument built for the collection.The teachers also answered a social-economic questionnaire that allowed the characterization of the research subjects.The theoretical support of the analysis is based on the logic that the subject s social construction happens through the generating principle of habitus (BOURDIEU s) that configures the dispositions constructed in the process (LAHIRE s) through the life and work trajectory and that respond by the interveners linked to the professional identities (DUBAR s). The bibliographical search demonstrates that the studies related to the theme find the importance of the socialization processes for the constitution of identities, take the educational politics as mechanism to explain the identity crisis and discuss the formation and the practices, in order to indicate the problems faced by the teachers in the school routine. However, studies in the sociological perspectives were not privileged, focusing the identity and the subject to decipher the structures of this matrix of perceptions and analyze how it interferes in the constitution of dispositions. The results show that the dispositions constructed by the teachers are deeply related to the structures of the habitus and that, although they have specificities linked to the singular interpretation that each of them express in their daily actions in the different contexts of professional insertion, they elapse from this generating principle. On the other hand, those dispositions, when in a showing-hiding game to answer the daily demands, show a tendency to maintain the regularities oriented by the habitus and promote an identity reconfiguration with disruptions and changes based on weak and temporary mobilizations. The study still reveals that the fact that the analysis privilege the teachers context of work implicates the use of the term identity forms , once that analysis is limited to a historical period and to a certain type of social context, constituted by individual and collective actionsthat respond for social constructions shared with everybody who have had similar trajectories, mainly in the professional field